Towards performance based design of drilled shafts. Issue 1 (April 2014) - Ng, K.
Abstract : For bridges or buildings that may be subjected to large vertical and lateral loads, drilled shafts offer an economical foundation solution. While current drilled shaft design practices are considered adequate, a performance based approach to drilled shaft design can be more cost effective and produce a more dependable response. This study examined a performance-based design concept using load test data from 24 usable drilled shafts from several states. The process identified a challenge: the Osterberg (O-cell) load test method was unable to characterize the full top load–displacement response. When a typical single O-cell is utilized in a drilled shaft test, depending on the location of the O-cell and the geomaterials present along and beneath the shaft, the load test result typically quantifies either the side resistance or the end bearing reaching the maximum load–displacement curve but not both. This limitation hinders the determination of a suitable shaft resistance as a function of target top displacement. To overcome this challenge, a procedure is proposed for establishing the full load–displacement curve based on data gathered from one O-cell. The method is presented for three different cases (i.e. side resistance reaches the maximum value during the test, end bearing reaches the maximum value during the test and neither component reaches the maximum value). Because it allows characterization of the full load–displacement curve, the proposed procedure enables a performance based design of drilled shafts with due consideration to settlement while satisfying Load and Resistance Factor Design requirements.